ACOUSTIC RADIATION ENERGY AT A VARIATION OF THE COMPOSITE MECHANICAL DESTRUCTION AREA - Filonenko, Sergii (Proceedings of National Aviation University (archive), 2016)
Purpose: The technological parameters of composite materials machining and also cutting tool state determine deforming and destruction of their surface layers conditions. Change of this conditions results to appearance of miscellaneous defects, loss of quality and produced items reliability. Therefore, optimization, control, diagnosis and monitoring of composite materials machining technological parameters are directed on obtaining the items given quality. For the solution of these problems tasks carry out researches of technological processes with usage of different methods. One of such methods is the acoustic emission method. Methods: The simulation and analysis of acoustic radiation energy parameters is carried out at change of composite material machining depth for prevailing mechanical destruction its surface layer. Results: We showed that to composite material machining the acoustic radiation energy has continuous nature. The ascending of composite material machining depth results to increase of acoustic emission statistical energy parameters. The regularity of acoustic emission energy parameters change are obtained and described. Is showed, that acoustic radiation most sensing parameter is the acoustic emission signals energy average level dispersion. Discussion: The outcomes researches demonstrate regularity influencing of composite material machining depth on acoustic emission energy parameters. Thus the analysis of acoustic emission signals energy average level dispersion can be used at mining methods of diagnostic, monitoring and control of composite materials machining technological parameters.